2016
DOI: 10.1177/0734242x16670000
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of excavated fine fraction and waste composition from a Swedish landfill

Abstract: The present research studies the characterisation and the physico-chemical properties of an excavated fine fraction (<10 mm) from a Swedish landfill, the Högbytorp. The results showed that the fine fraction represents 38% by mass of the total excavated wastes and it contains mainly soil-type materials and minerals. Higher concentrations of zinc, copper, barium and chromium were found with concentrations higher than the Swedish Environmental Protection Agency (EPA) for contaminated soil. The found moisture and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
39
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 24 publications
10
39
2
Order By: Relevance
“…The results showed that the rejected fraction was the highest with 65% of the total excavated wastes which represents large proportion of biodegradable waste and mineral waste as landfilled. This result was higher than described in previous studies conducted by Jani et al [3] with 27.3% and Hull et al [12] with 17.7% but it was in corresponding with results from studies of Siddiqui et al [14] with 58% and Quaghebeur et al [13] with 70%. However, the plastic and textile was the dominating fraction with 25% in the sorted masses, which can be considered as a source of recovering energy by incineration.…”
Section: Composition Of the Excavated Wastescontrasting
confidence: 56%
See 4 more Smart Citations
“…The results showed that the rejected fraction was the highest with 65% of the total excavated wastes which represents large proportion of biodegradable waste and mineral waste as landfilled. This result was higher than described in previous studies conducted by Jani et al [3] with 27.3% and Hull et al [12] with 17.7% but it was in corresponding with results from studies of Siddiqui et al [14] with 58% and Quaghebeur et al [13] with 70%. However, the plastic and textile was the dominating fraction with 25% in the sorted masses, which can be considered as a source of recovering energy by incineration.…”
Section: Composition Of the Excavated Wastescontrasting
confidence: 56%
“…As an example, about 50% of the extracted iron and copper along the industrial history are unusable due to landfilling [2]. Therefore, the landfill mining approach is of great importance to achieve a better sustainability of raw materials by returning these lost materials back to the circular economy [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations